The Analysis of Harmful Factors Affecting on Mental Health and Cognitive Function among Workers of Steel Industry (Using the ISO9612 Approach) - Hadi alimoradi; Mahsa Nazari; Reza Jafari Nodoushan; Alireza ajdani (Indian Journal of Psychiatric Nursing)
Background: In most industrial environments, workers are exposed to noise on a daily basis. The present study dealt with a set of cognitive factors to evaluate the negative emotional states in depression, anxiety, and stress in a noisy work environment. Methods: The research was a case-study that examined in 1000 male workers of steel industry. The sampling method was random sampling. The workers filled out questionnaire about, Depression, Anxiety, Stress, Scale, Cognitive Processing Inventory, and personality type tests in the study, and the ISO 9612:2009 standards was used to obtain external noise. Data were collected and analyzed using SPSS version 22 and exact test with 0.05 significant levels. Results: According to the results, age showed a significant effect on depression, marital status on anxiety, and the shift on employee stress (P < 0.05). Conclusion: Finally, one can conclude that given the positive and significant relationship between noise pressure level and cognitive and subjective components in the case group, it is necessary to take effective preventive measures to prevent psychological damage and to maintain workers' health in the industry.